Traumatic Events and PTSD Among Palestinian Children and Adolescents: The Effect of Demographic and Socioeconomic Factors - El-Khodary, Basel; Samara, Muthanna; Askew, Chris (Frontiers in Psychiatry, 2020)
Background: This study investigates the prevalence of traumatic events and Posttraumatic Stress Disorder (PTSD) among Palestinian children and adolescents in the Gaza Strip. Methods: The sample consists of 1029 school pupils (11-17 years old): 533 (51.8%) were female and 496 (48.2%) were male. War-Traumatic Events Checklist (W-TECh) Post-Traumatic Stress Disorders Symptoms Scale (PTSDSS) were used. Results: 88.4% (N = 909) experienced personal trauma, 83.7% (N = 861) witnessed trauma to others, and 88.3% (N = 908) observed demolition of property during the war. Compared to girls, boys showed significantly more exposure to all three event types as well as overall traumatic events. Results also demonstrated that the prevalence of DSM-V PTSD diagnosis was 53.5% (N = 549). Further, children who had experienced personal trauma, trauma to others, and the demolition of property were significantly more likely to be diagnosed with PTSD compared to those who had not even when adjusting for demographic and socioeconomic factors.